The parameters of homemade jams after storage - Diósi, Gerda; Sipos, Péter (Acta Agraria Debreceniensis, 2014)
Nowadays producing jams is considered a traditional way of plum processing in Hungary. Plum jams without added sugar can be stored This research aimed to analytically determine which quality parameters of the jams and to what extent they change during storage. Furthermore, this study intended to find out whether a concious consumer can presume any difference between varieties or the year of harvest, or wheather a one-time customer should suspect differences in quality parameters of the different products. This study focused on those differences or alterations in the parameters that occur in the jams made from several different plum varieties produced in different years. I analyzed the classic chemical parameters (dry matter content and ash content) and physiologically important nutritional components (phenolic and flavonoids antioxidants and vitamin C). In this research I used jams which were produced from 6 varieties grown in 2009 (President, Tophit, Bluefre, Elena, Presenta, Stanley), 4 varieties from 2010 (President, Bluefre, Elena, Presenta) and 6 varieties from 2011 (President, Tophit, Bluefre, Elena, Presenta, Stanley). Jams were produced with traditional technology in cauldrons without added sugar. Jars were placed into a relatively dark and cool place and were stored there until the analysis. Having regard to the results, when consumers choose between the different products they also choose quality since the processed plum variety, and the year of production/processing determine the nutritional value of the specific product. This could be used for market positioning and promotion of the product, however further research is needed to gain more information from the differences that derive from the varieties, year of harvest or other factors. This way fruit and jam producers could turn these informations into market advantage.